Anti-nociceptive effect of seed extract of Acacia tortilis in rodents - Agrawal, Neeraj K.; Gupta, Uma; Kothari, Nitin; Chandra, Shruti; Singh, Rashmi; Pandey, Shubham (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Management of pain is a primary clinical concern for any pathology in medical field. Addiction liability of opioids and troublesome gastrointestinal side effects of NSAIDs leads to intensive research for compound with lesser side effects.The aim of the study to evaluate the anti-nociceptive activity of Acacia Tortilis Seed Extract (ATE) in experimental animals. Methods: First of all, animals were randomly allocated into four groups of six animals each. In acetic acid induced writhing test model, Group I (NC) served as vehicle control received saline/Tween 80 0.1%, 10ml/kg BW orally, group II (ATE-100) and III (ATE-200) received ATE in dose of 100 and 200mg/kg BW orally respectively and group IV received the standard drug diclofenac sodium in dose of 50 mg/kg BW orally. Group I to IV were same in rest of three experimental models. One additional group of standard drugs (group V) morphine sulfate in dose of 5 mg/kg BW subcutaneously (SC) was allocated for screening method hot plate and tail flick tests. In Formalin induced paw licking test, three additional groups (group V) morphine sulfate in dose of 5mg/kg BW SC, group VI- morphine+naloxone (5mg/kg SC +2mg/kg intra-peritoneally (IP) and group VII - ATE+ naloxone (200mg/kg BW orally +2mg/kg BW IP) were also made. Results: The ATE when administered orally in dose of 100 and 200mg/ kg body weight (BW), produced significant analgesic activity (P <0.01) in acetic acid induced writhing syndrome and late phase of formalin test. In the hot plate test in mice and tail flick test in rats, ATE in same doses also showed significant analgesic activity (P <0.05) which is almost equally efficacious to standard drug diclofenac sodium (50mg/kg BW orally) but far less efficacious than morphine sulfate (5mg/kg BW subcutaneous).ATE (200mg/Kg BW orally) activity did not blocked by naloxone (2mg/kg intra-peritoneal). Conclusions: ATE possesss significant anti-nociceptive activity as evidenced in all the animal models of nociception. It might exert its effect through the peripheral mechanism of analgesic action possibly by interference in biosynthesis, release and/or action of prostaglandins and leukotrienes.